Etiological Spectrum of Surgical Acute Abdomen among patients attending Emergency Department - Aamir Jameel, Imran Anwar, Muhammad Hamza Laique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute abdomen is a common health issue that ranges from trivial to life threatening condition thus requiring hospital admissions, correct diagnosis and treatment. Aim: To determine the etiological spectrum of surgical acute pain abdomen among patients attending emergency department at government hospital-Lahore. Study design: Cross sectional study. Methodology: Present study enrolled both genders (n=154) through simple random sampling technique following ethical approval. All baseline investigations were done at time of enrollment. All information was collected through structured questionnaire. Radiological investigations like ultrasonography (USG) and computer tomography (CT) scan were done on appropriate indication. Data was evaluated by using SPSS v.24. Chi-square test was used to compare the symptoms, diagnosis, treatments and clinical signs between the both genders. A p-value ≤0.05 was considered significant. Results: Mean age of the patients was 41.4±16.5 years. There were 82(53.2%) males and 72(46.8%) females. Symptoms like abdominal pain, burning micturation, diarrhea and guarding were significantly higher in males. The proportion of localized pain was higher in female as compared to male but statistically insignificant. Practical Implication: As there is a high incidence of acute abdomen among our population and there is lack of local data regarding exact epidemiology of this health issue. The findings of this study emphasized the etiological spectrum of acute surgical abdomen. This helped in pointing out the loop holes regarding correct diagnosis while identifying different presentations of serious illnesses. Conclusion: It was concluded that patients present differently with acute abdomen so common diagnosis should be made and prompt examination need to be done. Timely intervention and management can therefore prevent major complications. Keywords: Acute abdomen, Appendicitis, Perforation peritonitis and Surgical Intervention